Ursolic acid induces cell death and modulates autophagy through JNK pathway in apoptosis-resistant colorectal cancer cells - Xavier, Cristina P. R. (2013)
Colorectal carcinomas (CRCs) with P53 mutations have been shown to be resistant to chemotherapy with 5-fluorouracil (5-FU), the most widely used chemotherapeutic drug for CRC treatment. Autophagy is emerging as a promising therapeutic target for drug-resistant tumors. In the present study, we tested the effects of ursolic acid (UA), a natural triterpenoid, on cell death mechanisms and its effects in combination with 5-FU in the HCT15 p53 mutant apoptosis-resistant CRC cell line. The involvement of UA in autophagy and its in vivo efficacy were evaluated. Our data show that UA induces apoptosis independent of caspases in HCT15 cells and enhances 5-FU effects associated with an activation of c-jun N-terminal kinase (JNK). In this cell line, where this compound has a more pronounced effect on the induction of cell death compared to 5-FU, apoptosis corresponds only to a small percentage of the total cell death induced by UA. UA also modulated autophagy by inducing the accumulation of LC3 and p62 levels with involvement of JNK pathway, which indicates a contribution of autophagy on JNK-dependent induction of cell death by UA. By using nude mice xenografted with HCT15 cells, we verified that UA was also active in vivo decreasing tumor growth rate. In conclusion, this study shows UA's anticancer potential both in vitro and in vivo. Induction of cell death and modulation of autophagy in CRC-resistant cells were shown to involve JNK signaling.